The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0163278717735565
|View full text |Cite
|
Sign up to set email alerts
|

Using Generalizability Theory to Inform Optimal Design for a Nursing Performance Assessment

Abstract: The promotion of competency of nurses and other health-care professionals is a goal shared by many stakeholders. In nursing, observation-based assessments are often better suited than paper-and-pencil tests for assessing many clinical abilities. Unfortunately, few instruments for simulation-based assessment of competency have been published that have undergone stringent reliability and validity evaluation. Reliability analyses typically involve some measure of rater agreement, but other sources of measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…67 Studies in veterinary and nursing education have reported successfully using fewer than 20 persons in conjunction with larger number of conditions per facet. 52,68 The small sample size may have contributed to the observed low variance in student scores as assessed by the checklist. If the surgical skills examination on a model, scored using the checklist, is to be used as a high-stakes assessment, particularly at other institutions, further validity evidence and additional reliability data should be gathered to maintain a solid validity argument for its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Studies in veterinary and nursing education have reported successfully using fewer than 20 persons in conjunction with larger number of conditions per facet. 52,68 The small sample size may have contributed to the observed low variance in student scores as assessed by the checklist. If the surgical skills examination on a model, scored using the checklist, is to be used as a high-stakes assessment, particularly at other institutions, further validity evidence and additional reliability data should be gathered to maintain a solid validity argument for its use.…”
Section: Discussionmentioning
confidence: 99%
“…While specific guidelines on minimal sample size for generalizability studies have not been established, a minimum of 20 persons for a 1 facet design has been suggested 67 . Studies in veterinary and nursing education have reported successfully using fewer than 20 persons in conjunction with larger number of conditions per facet 52,68 . The small sample size may have contributed to the observed low variance in student scores as assessed by the checklist.…”
Section: Discussionmentioning
confidence: 99%
“…G Theory simultaneously facilitates the identification of multiple sources of variance and quantification of each individual variance in a measurement (Bloch & Norman, 2012;Briesch, Swaminathan, Welsh, & Chafouleas, 2014). Based on a variance component analysis (Brennan, 2010), it differentiates the sources of variance and estimates the magnitude of each variance (O'Brien, Thompson, & Hagler, 2017).…”
Section: Generalisability Theorymentioning
confidence: 99%
“…biases and poorly-constructed marking criteria (Prion et al, 2016). The major limitation of using CTT in reliability analyses is that it focuses on only a single source of error variance at any one time (Bloch & Norman, 2012), as it does not differentiate sources of error variance (O'Brien et al, 2017).…”
Section: An Overview Of Generalisability Theory (G Theory)mentioning
confidence: 99%
See 1 more Smart Citation